2012
DOI: 10.30552/ejep.v5i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Test de Fluidez Verbal: datos normativos y desarrollo evolutivo en el alumnado de primaria

Abstract: El objetivo principal de este estudio consistió en la baremación y el análisis del desarrollo evolutivo, en una amplia muestra de población infantil de habla española, de dos pruebas destinada a la evaluación de la fluidez verbal (semántica y fonológica). Analizamos el desarrollo de ambas tareas dentro de un contexto de diseño transversal. Se seleccionó una muestra de 1.032 sujetos con edades comprendidas entre los 6 años y 3 meses y los 12 años y cuatro meses que cursaban entre primero y sexto de educación pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 39 publications
5
25
0
13
Order By: Relevance
“…A healthy adult can produce around 12 and 16 words per minute in phonological and semantic VFT, respectively (Spreen & Strauss, 1998). As mentioned previously performance on both phonological and semantic tasks increases with age among young children (García et al, 2012;Matute, Rosselli, Ardila, & Morales, 2004;Riva, Nichelli, & Devoti, 2000;Van der Elst et al, 2011). Children between the ages of 6 and 8 produce between 3 and 12 words in phonological VFT, whereas children between 6 and 12 years can generate as many as 10 to 15 animals in a semantic VFT (Matute et al, 2004).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…A healthy adult can produce around 12 and 16 words per minute in phonological and semantic VFT, respectively (Spreen & Strauss, 1998). As mentioned previously performance on both phonological and semantic tasks increases with age among young children (García et al, 2012;Matute, Rosselli, Ardila, & Morales, 2004;Riva, Nichelli, & Devoti, 2000;Van der Elst et al, 2011). Children between the ages of 6 and 8 produce between 3 and 12 words in phonological VFT, whereas children between 6 and 12 years can generate as many as 10 to 15 animals in a semantic VFT (Matute et al, 2004).…”
Section: Introductionmentioning
confidence: 55%
“…Several variables have been associated with performance on VFT, but in the case of children and adolescents, the most significant variable is age (Beltrán Dulcey & Solís-Uribe, 2012;García et al, 2012;Lozano & Ostrosky-Solís, 2006;Malloy-Diniz et al, 2007;Martins, Mograbi, Andrade Gabrig, & Charchat-Fichman, 2016;Nieto, Galtier, Barroso, & Espinosa, 2008;Prigatano, Gray, & Lomay, 2008;Ruffieux et al, 2009;Tallberg, Carlsson, & Lieberman, 2011;Van der Elst, Hurks, Wassenberg, Meijs, & Jolles, 2011). Past research has consistently found that older children perform better on VFT.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations